2006
DOI: 10.1002/erv.769
|View full text |Cite
|
Sign up to set email alerts
|

Exercise behaviours and feelings in eating disorder and non‐eating disorder groups

Abstract: Clinicians assessing eating disordered individuals should address specific exercise feelings, rather than exercise amount or frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
54
0
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 16 publications
11
54
0
7
Order By: Relevance
“…3,5 The difference between patients and controls regarding exercise for negative affect regulation is consistent with previous studies. 4,13 The lack of difference in exercise for weight/appearance is consistent with the study of Boyd et al 4 We cannot exclude that the patients deliberately underestimated the importance of exercise for weight and shape due to the inpatient treatment setting. Also, reasons for exercise may vary over time.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…3,5 The difference between patients and controls regarding exercise for negative affect regulation is consistent with previous studies. 4,13 The lack of difference in exercise for weight/appearance is consistent with the study of Boyd et al 4 We cannot exclude that the patients deliberately underestimated the importance of exercise for weight and shape due to the inpatient treatment setting. Also, reasons for exercise may vary over time.…”
Section: Discussionsupporting
confidence: 73%
“…Empirically, the findings are inconsistent. [1][2][3][4] Among the different ED diagnoses, patients with anorexia nervosa (AN) have been found more physically active when compared with bulimia nervosa (BN), 3,5 whereas information about patients with ED not otherwise specified (EDNOS) is lacking. One possible explanation for the inconsistent findings is the use of different assessment methods for physical activity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While preoccupation with exercise in the eating disorders has in the main been associated with weight-and body shape concerns (Brewerton et al, 1995;Shroff et al, 2006;, studies have shown that the regulation of negative emotions makes an important contribution to compulsive exercise in patients with anorexia nervosa (Boyd, Abraham, & Luscombe, 2007;Bratland-Sanda et al, 2011;Bratland-Sanda et al, 2010a;Lawson, Waller, & Lockwood, 2007;Meyer & Taranis, 2011). Conventional biomedical approaches assume that women with anorexia have difficulty identifying and regulating their emotions (Gilboa-Schechtman, Avnon, Zubery, & Jeczmien, 2006;Oldershaw et al, 2011;Oldershaw, Hambrook, Tchanturia, Treasure, & Schmidt, 2010), particularly in the restricting type (Harrison, Sullivan, Tchanturia, & Treasure, 2010).…”
Section: Compulsive Exercise and Anorexia Nervosamentioning
confidence: 99%